Casting preparation method of multi-layer fluorescent microcrystalline glass based on in-situ compounding

By using an in-situ composite casting method, a tight interfacial bond is achieved in multilayer fluorescent glass crystals, which solves the problem of insufficient interlayer bonding strength in traditional processes, improves optical performance and mechanical reliability, and is suitable for high-precision optoelectronic devices.

CN121426421APending Publication Date: 2026-01-30XUZHOU NORMAL UNIVERSITY +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511706283.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-20
Publication Date
2026-01-30

AI Technical Summary

Technical Problem

In existing multilayer fluorescent glass-ceramic fabrication processes, insufficient interlayer bonding strength and poor interface compactness lead to delamination, cracking, and poor optical performance, making it difficult to meet the high precision requirements of ultrathin optoelectronic devices.

Method used

An in-situ composite casting method was adopted, and molecular-level penetration and chemical bonding of multilayer fluorescent microcrystalline glass were achieved through gradient drying and co-sintering treatment to form a tight interface bond.

Benefits of technology

It significantly improves the interfacial bonding stability and optical performance of multilayer structures, reduces production costs, and meets the precision size and optical purity requirements of ultrathin optoelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121426421A_ABST
    Figure CN121426421A_ABST
Patent Text Reader

Abstract

The invention discloses a tape casting preparation method of multi-layer fluorescent microcrystalline glass based on in-situ compounding, and belongs to the technical field of functional glass ceramic composite material preparation. The method aims at solving the problems that in a traditional lamination process, the interface bonding force is weak, layering is prone to occurring, and the optical performance is damaged, the core step of the method is a one-step composite forming process after gradient drying and in-situ tape casting, and a prepared multi-layer fluorescent microcrystal composite green body is subjected to programmed glue discharging and co-sintering treatment; the multi-layer fluorescent microcrystalline glass with a compact interface and good optical performance is successfully obtained. Through the in-situ tape casting composite technology, tight combination between interface layers is achieved, interface pores and light scattering centers are effectively reduced, the mechanical strength, thermal stability, fluorescence luminous efficiency and uniformity of the material are remarkably improved, and the material is suitable for advanced photoelectric devices for full-spectrum healthy lighting, high-power LEDs, laser lighting and the like.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of functional glass ceramic composite material preparation, in particular to a flow casting preparation method of multilayer fluorescent glass ceramic based on in-situ compounding. BACKGROUND

[0002] As a functional material with both glass properties and crystal luminescence characteristics, fluorescent glass ceramic shows great application potential in the field of optoelectronic devices such as LED display, automotive lighting and high-end projection. By uniformly dispersing fluorescent powder in the glass matrix and undergoing crystallization treatment, it can solve the problems of serious high-temperature light decay and short service life caused by traditional organic resin packaging materials, and also achieve precise control of the luminescence spectrum.

[0003] At present, the preparation of multilayer fluorescent glass ceramic mainly adopts the traditional laminated sintering process, that is, first flow casting each layer of green body, drying, cutting and then manually stacking and sintering as a whole. However, this process has significant defects: first, air gaps and environmental impurities are easily left between layers, resulting in insufficient interfacial bonding strength, and the sample is prone to delamination and cracking during subsequent use, which seriously reduces the mechanical reliability; second, the warping and irregular edge problems during the sintering process of independent green bodies easily cause alignment deviation during stacking, making it difficult to precisely control the thickness tolerance, which cannot meet the high precision requirements of ultra-thin optoelectronic devices. In addition, the existing technologies have not effectively solved the problems of interfacial bonding strength, density and optical purity of multilayer fluorescent glass ceramic.

[0004] Therefore, it is a technical problem to be solved in the field of functional glass composite materials to develop a multilayer fluorescent glass ceramic preparation method that can realize tight interlayer bonding, controllable size precision, and consider both optical performance and large-scale production. The flow casting preparation method of multilayer fluorescent glass ceramic based on in-situ compounding provided by the present application breaks through the inherent defects of the traditional laminated sintering process and constructs a continuous preparation process based on in-situ compounding, which is one of the core paths to solve the above technical bottlenecks. SUMMARY

[0005] One of the purposes of the present application is to provide a flow casting preparation method of multilayer fluorescent glass ceramic based on in-situ compounding, which flow casts an integrated green body with a multilayer structure through in-situ compounding, promotes molecular-level penetration and chemical bonding between layers, significantly improves the interfacial bonding stability of the multilayer structure, and can control the thickness of each layer and the overall size tolerance, meeting the stringent requirements of ultra-thin optoelectronic devices for material structural integrity and precise dimensions.

[0006] The second object of the present application is to construct a modular continuous flow in-situ composite system, which can flexibly increase or decrease the number of functional layers, replace different types of fluorescent slurry or glass slurry according to actual needs, and adapt to the core components of existing flow casting equipment without large-scale modification of the production line, thereby improving the universality and flexible expansion of the process and meeting the needs of rapid update iteration of diversified products.

[0007] In order to achieve the above object, the technical scheme adopted by the present application is as follows: a flow casting preparation method of multi-layer fluorescent microcrystalline glass based on in-situ composite, the core step of which is a one-step in-situ flow casting composite forming process after gradient drying, and the multi-layer fluorescent microcrystalline composite green body obtained by the preparation is subjected to programmed degassing and co-sintering treatment, so that a multi-layer fluorescent microcrystalline glass with dense interface and good optical performance is successfully obtained.

[0008] The present application provides a flow casting preparation method of multi-layer fluorescent microcrystalline glass based on in-situ composite, which specifically comprises the following steps: (1) preparing flow casting slurry: yellow fluorescent microcrystalline glass (Yellow PGC) slurry, red fluorescent microcrystalline glass (Red PGC) slurry and pure glass slurry are prepared respectively, wherein the yellow fluorescent microcrystalline glass slurry and the red fluorescent microcrystalline glass slurry are prepared by ball milling low-temperature transparent glass powder, fluorescent powder, dispersing agent, binder and organic solvent in a mass ratio and then centrifuging at high speed to remove bubbles.

[0009] (2) in-situ flow casting and gradient drying: the yellow fluorescent microcrystalline glass slurry prepared in step (1) is introduced into the first scraper material tank of the flow casting equipment, and after being formed by a scraper, it is sent to the first drying box body, and then after drying, it is sent to the second flow casting by a conveying belt to obtain the first green body.

[0010] (3) the red fluorescent microcrystalline glass slurry prepared in step (1) is introduced into the second scraper material tank of the flow casting equipment, and after in-situ composite flow casting with the first green body prepared in step (2), it is sent to the second drying box body, and then after drying, it is sent to the third flow casting by a conveying belt to obtain the second green body.

[0011] (4) the pure glass slurry prepared in step (1) is introduced into the third scraper material tank of the flow casting equipment, and after in-situ composite flow casting with the second green body prepared in step (3), it is sent to the third drying box body, and then after drying, it forms an integrated composite green body, and finally flows out with the conveying belt.

[0012] (5) degassing and sintering treatment: the integrated composite green body after drying is placed in a muffle furnace, and the temperature is first raised to 400-600 DEG C at a heating rate of 0.5-5 DEG C / min, degassing for 4-20 h, then raised to 600-900 DEG C, and kept for 1-6 h, and finally cooled to room temperature with the temperature, so that a multi-layer fluorescent microcrystalline glass composite luminescent material with tight interface bonding is obtained.

[0013] Preferably, in step (1), the chemical formula of the low-mid temperature transparent glass powder is a1%SiO2-a2%P2O5-a3%B2O3-a4%Al2O3-a5%BaO-a6CaO-a7%K2O-a8%Na2O, wherein 0 < a1 < 100, 0 < a2 < 100, 0 < a3 < 100, 0 < a4 < 100, 0 < a5 < 100, 0 < a6 < 100, 0 < a7 < 100, 0 < a8 < 100, and the ratio coefficients in the compound satisfy a1+a2+a3+a4+a5+a6+a7+a8=100, and the fluorescent powder is at least one of YAG:Ce, CaAlSiN3:Eu, CaSrAlSiN3:Eu, Lu3Al5O 12 :Ce.

[0014] Preferably, in step (1), the dispersant is ammonium polyacrylate or sodium hexametaphosphate, the binder is polyvinyl butyral or methyl cellulose, and the organic solvent is at least one of ethanol, acetone and oleic acid.

[0015] Preferably, in steps (2), (3) and (4), the temperature of the drying box is 50-100℃, and the winding speed of the conveying belt is 20-120cm / min.

[0016] Preferably, in steps (2), (3) and (4), the base height of the doctor blade is 100-300μm, and the thickness of each layer of the green body is controlled to be 50-200μm by increasing the height of the doctor blade by 50-200μm in each subsequent casting process.

[0017] Preferably, the chemical formula of the low-mid temperature transparent glass powder is 55%SiO2-12%P2O5-18%B2O3-3.5%Al2O3-4%BaO-3%CaO-2.5%K2O-2%Na2O.

[0018] Compared with the prior art, the present application has the following beneficial effects: 1. The present application provides a casting preparation method for multilayer fluorescent microcrystalline glass based on in-situ compounding. Compared with the traditional solid dry stacking process, the present application realizes the close combination between molecular layers in the green body stage, basically eliminates the air gap between layers, and after the sample is subjected to co-sintering treatment, the obtained interface is dense and has no delamination, and the bonding strength is improved by orders of magnitude. Moreover, the dense interface not only greatly enhances the thermal shock resistance and mechanical reliability of the material, but also reduces the light scattering loss at the interface, thereby providing photoelectric devices with higher light output efficiency and more excellent optical quality.

[0019] 2.The application provides a kind of based on in-situ composite multilayer fluorescent glass-ceramics flow preparation method, compared to dry method stacking technology exists independent blank drying, cutting, superposition etc. Multiple processes, long production cycle and manual superposition is prone to alignment deviation, resulting in product thickness tolerance difficult to control and other problems. The application adopts modular in-situ composite continuous flow forming process, realizes the in-situ forming of multilayer blank and integrated drying and co-sintering treatment, promotes one-step forming process to be more simple. In addition, continuous flow forming reduces blank cutting waste, combined with fluorescent powder surface modification and gradient process design, while ensuring high performance of the product, significantly reduces production cost, has stronger industrial application competitiveness. BRIEF DESCRIPTION OF DRAWINGS

[0020] Figure 1 A flow preparation schematic diagram of multilayer fluorescent glass-ceramics based on in-situ composite is provided for the embodiment 1 of the application.

[0021] Figure 2 A cross-sectional optical micrograph comparison chart of yellow-pure glass double-layer fluorescent glass-ceramics sintered and formed by traditional dry method stacking process and in-situ composite flow process provided by the embodiment 2 is provided.

[0022] Figure 3 An optical micrograph of the cross section of yellow-red fluorescent glass in-situ composite flow blank after sintering is provided for the embodiment 3 of the application.

[0023] Figure 4 A luminescence spectrum of LED packaged by yellow-red fluorescent glass provided for the embodiment 3 of the application. DETAILED DESCRIPTION

[0024] The application will be further described in detail below in combination with the drawings and specific embodiments.

[0025] It should be pointed out that the following embodiments will help those skilled in the art to further understand the application, but do not limit the application in any form.

[0026] Embodiment 1

[0027] Yellow-red-pure glass multilayer fluorescent glass-ceramics is prepared.

[0028] (1) Preparation of casting slurry: 18wt.% yellow fluorescent glass-ceramics (Yellow PGC) slurry, 18wt.% red fluorescent (CaAlSiN3:Eu) glass-ceramics slurry and pure glass slurry were prepared respectively, wherein the yellow fluorescent glass-ceramics slurry and the red fluorescent glass-ceramics slurry were prepared by ball milling the low-melting transparent glass powder, fluorescent powder, dispersant, binder and organic solvent in a mass ratio and then centrifuging at high speed to remove bubbles, and the chemical formula of the low-melting transparent glass powder was 55%SiO2-12%P2O5-18%B2O3-3.5%Al2O3-4%BaO-3%CaO-2.5%K2O-2%Na2O, and the pure glass slurry was prepared by ball milling the low-melting transparent glass powder, dispersant, binder and organic solvent in a mass ratio and then centrifuging at high speed to remove bubbles.

[0029] (2) In-situ casting and gradient drying: the yellow fluorescent glass-ceramics slurry prepared in step (1) was introduced into the first-stage doctor blade tank of the casting equipment, the doctor blade height was 120μm, the winding speed was 50cm / min, and after being shaped by the doctor blade, it was sent to the first-stage drying box, and then was sent to the second-stage casting by the conveying belt after drying, to obtain the first-stage green body.

[0030] (3) The red fluorescent glass-ceramics slurry prepared in step (1) was introduced into the second-stage doctor blade tank of the casting equipment, the doctor blade height was 240μm, the winding speed was 50cm / min, and after being in-situ compound casted with the first-stage green body prepared in step (2), it was sent to the second-stage drying box, and then was sent to the third-stage casting by the conveying belt after drying, to obtain the second-stage green body.

[0031] (4) The pure glass slurry prepared in step (1) was introduced into the third-stage doctor blade tank of the casting equipment, the doctor blade height was 360μm, the winding speed was 50cm / min, and after being in-situ compound casted with the second-stage green body prepared in step (3), it was sent to the third-stage drying box, and then formed an integrated compound green body after drying, and finally flowed out of the conveying belt.

[0032] (5) Glue removal and sintering treatment: the integrated compound green body after drying was placed in a muffle furnace, and the temperature was first increased to 530℃ at a rate of 2℃ / min, and the glue was removed for 10h, then the temperature was increased to 750℃, and the temperature was kept for 3h, and finally the temperature was cooled to room temperature, to obtain a multi-layer fluorescent glass-ceramics composite luminescent material with a tight interface bonding.

[0033] Figure 1A process flow diagram for preparing a multilayer fluorescent glass-ceramic composite material in this example based on in-situ compounding is shown. The process uses a modular in-situ compounding continuous casting process to achieve in-situ forming and integrated drying of the multilayer body, making the one-step forming process more convenient. In addition, continuous casting reduces waste from cutting the body. Combined with surface modification of the fluorescent powder and gradient process design, the preparation cost is significantly reduced while ensuring high performance of the product, which has great application prospects in industrial production.

[0034] Example 2

[0035] A yellow-pure glass double-layer fluorescent glass-ceramic was prepared.

[0036] (1) Preparation of casting slurry: 26wt.% yellow fluorescent glass-ceramic (Yellow PGC) slurry and pure glass slurry were prepared respectively. The yellow fluorescent glass-ceramic slurry was prepared by ball milling low-temperature transparent glass powder, fluorescent powder, dispersant, binder and organic solvent in a certain mass ratio and then centrifuging to remove bubbles. The chemical composition of the low-temperature transparent glass powder is 55% SiO2-12% P2O5-18% B2O3-3.5% Al2O3-4% BaO-3% CaO-2.5% K2O-2% Na2O.

[0037] (2) In-situ casting and gradient drying: The yellow fluorescent glass-ceramic slurry prepared in step (1) was introduced into the first-stage doctor blade trough of the casting equipment, with a doctor blade height of 150 μm and a winding speed of 45 cm / min. After casting, it was sent to the first-stage drying box, and then to the second-stage casting with a conveyor belt after drying, to obtain a yellow green body.

[0038] (3) The pure glass slurry prepared in step (1) was introduced into the second-stage doctor blade trough of the casting equipment, with a doctor blade height of 300 μm and a winding speed of 45 cm / min. After in-situ compounding casting with the yellow green body prepared in step (2), it was sent to the second-stage drying box, and then to the second-stage casting with a conveyor belt after drying, to form an integrated composite green body, and finally to flow out.

[0039] (4) Glue removal and sintering treatment: The integrated composite green body after drying was placed in a muffle furnace, first raised to 520℃ at a heating rate of 2℃ / min, degreased for 8h, then raised to 750℃, and kept for 3h, and finally cooled to room temperature with the temperature, to obtain a yellow-pure glass double-layer fluorescent glass-ceramic with tight interface bonding.

[0040] Figure 2The cross-section optical micrographs of sintered 26wt.% yellow-pure glass double-layer fluorescent glass-ceramics prepared by the traditional dry lamination process and the in-situ composite casting process provided in the present example are shown respectively. In the sample of the traditional dry lamination process shown in the left figure, an obvious interlayer gap can be observed in the red box, and there are more pores or non-uniform regions in the interlayer and interior, which leads to a decrease in optical performance. At the same time, there is a physical separation caused by the independent blank body superimposed at the interface, which will cause insufficient interlayer bonding and easy delamination and cracking in subsequent use. In the sample of the in-situ composite casting process provided in the present example shown in the right figure, the interlayer interface is completely fused, and there is no obvious pore defect in the red box. This is because the in-situ casting composite process enables the interlayer penetration and infiltration of the molecular layers of each layer of slurry, forming an integrated blank, which ensures the close bonding of the interface from the microstructure, significantly improves the structural integrity and mechanical reliability of the material, and can ensure higher light transmission and luminous efficiency, while making the light field distribution more uniform and controllable.

[0041] Example 3

[0042] Yellow-red double-layer fluorescent glass-ceramics were prepared.

[0043] (1) Casting slurry preparation: 22wt.% yellow fluorescent (YAG:Ce) glass-ceramic slurry and 32wt.% red fluorescent (CaAlSiN3:Eu) glass-ceramic slurry were prepared respectively, wherein the yellow fluorescent glass-ceramic slurry and the red fluorescent glass-ceramic slurry were prepared by ball milling low-temperature transparent glass powder, fluorescent powder, dispersant, binder and organic solvent in a mass ratio and then centrifuging at high speed to remove bubbles.

[0044] (2) In-situ casting and gradient drying: the yellow fluorescent glass-ceramic slurry prepared in step (1) was introduced into the first section of the doctor blade trough of the casting equipment, the doctor blade height was 140μm, and the winding speed was 45cm / min. After being formed by the doctor blade, it was sent to the first section of the drying box, and then sent to the second section of the casting by the conveying belt after drying, to obtain the yellow green body.

[0045] (3) The red fluorescent glass-ceramic slurry prepared in step (1) was introduced into the second section of the doctor blade trough of the casting equipment, the doctor blade height was 320μm, and the winding speed was 45cm / min. After in-situ composite casting with the yellow green body prepared in step (2), it was sent to the drying box, and then formed into an integrated composite green body after drying, and finally flowed out with the conveying belt.

[0046] (4) Glue removal and sintering treatment: the double-layer composite green body after drying was placed in a muffle furnace, and the temperature was first raised to 520℃ at a rate of 2℃ / min, and the glue was removed for 8h, then the temperature was raised to 750℃, and the temperature was kept for 3h, and finally the temperature was cooled to room temperature. Yellow-red double-layer fluorescent glass-ceramics with tight interface bonding were obtained.

[0047] Figure 3The optical microscope photograph of the section of the yellow-red fluorescent glass prepared in the present example after sintering of the in-situ composite flow body is given, the yellow-red interface is completely fused, there is no obvious pore defect, the densification degree is improved, the structural integrity and mechanical reliability of the material are significantly improved, the loss of light in the material is reduced, and the fluorescent conversion efficiency and optical uniformity are improved. As shown in Figure 4 , the luminescence spectrum of the yellow-red double-layer fluorescent glass provided by the present example is measured, which shows that it has low color temperature and high color rendering index, and has great research value in the fields of high-power LED, automobile lighting and special lighting.

[0048] Example 4

[0049] Yellow-red-green-pure glass multilayer fluorescent glass is prepared.

[0050] (1) Preparation of flow slurry: 36wt.% yellow fluorescent (YAG:Ce) glass-ceramic slurry, 18wt.% red fluorescent (CaAlSiN3:Eu) glass-ceramic slurry, 18wt.% green fluorescent (Lu3Al5O 12 :Ce) glass-ceramic slurry and pure glass slurry are prepared, wherein the yellow fluorescent glass-ceramic slurry, the red fluorescent glass-ceramic slurry and the green fluorescent glass-ceramic slurry are all prepared by ball milling the low-temperature transparent glass powder, the fluorescent powder, the dispersing agent, the binder and the organic solvent in a mass ratio and then centrifuging to remove bubbles.

[0051] (2) In-situ flow and gradient drying: the yellow fluorescent glass-ceramic slurry prepared in step (1) is introduced into the first section of the doctor blade material tank of the flow equipment, the doctor blade height is 120μm, the winding speed is 55cm / min, after forming by the doctor blade, it is sent to the first section of the drying box, and then it is sent to the second section of the flow by the conveying belt after drying, to obtain the first section of the green body.

[0052] (3) The red fluorescent glass-ceramic slurry prepared in step (1) is introduced into the second section of the doctor blade material tank of the flow equipment, the doctor blade height is 240μm, the winding speed is 55cm / min, and the first section of the green body prepared in step (2) is in-situ composite flow after flow, and then it is sent to the second section of the drying box, and then it is sent to the third section of the flow by the conveying belt after drying, to obtain the second section of the green body.

[0053] (4) The green glass slurry prepared in step (1) is introduced into the third section of the doctor blade material tank of the flow equipment, the doctor blade height is 360μm, the winding speed is 55cm / min, and the second section of the green body prepared in step (3) is in-situ composite flow after flow, and then it is sent to the third section of the drying box, and then it is sent to the fourth section of the flow by the conveying belt after drying.

[0054] (5) The prepared pure glass slurry in step (1) is introduced into the fourth section of the doctor blade material tank of the casting equipment, the doctor blade height is 480 μm, the winding speed is 55 cm / min, and the third section of the green body prepared in step (4) is in-situ composite casted and sent into the fourth section of the drying box, dried to form an integrated composite green body, and finally sent out with the conveying belt.

[0055] (6) The dried integrated composite green body is placed in a muffle furnace, first raised to 540℃ at a heating rate of 2℃ / min, degassed for 12h, then raised to 750℃, kept for 4h, and finally cooled to room temperature with the temperature, to obtain yellow-red-green-pure glass multilayer fluorescent microcrystalline glass with a tight interface bonding.

[0056] The above is only a specific embodiment of the present application, but the protection scope of the present application is not limited thereto, any modification, equivalent replacement, improvement and supplement within the technical range disclosed by the present application, and any modification, equivalent replacement, improvement and supplement within the technical range disclosed by the present application, and any modification, equivalent replacement, improvement and supplement within the technical range disclosed by the present application, and any modification, equivalent replacement, improvement and supplement within the technical range disclosed by the present application, and any modification, equivalent replacement, improvement and supplement within the technical range disclosed by the present application, and any modification, equivalent replacement, improvement and supplement within the technical range disclosed by the present application, and any modification, equivalent replacement, improvement and supplement within the technical range disclosed by the present application, and any modification, equivalent replacement, improvement and supplement within the technical range disclosed by the present application, and any modification, equivalent replacement, improvement and supplement within the technical range disclosed by the present application, and any modification, equivalent replacement, improvement and supplement within the technical range disclosed by the present application, and any modification, equivalent replacement, improvement and supplement within the technical range disclosed by the present application, and any modification, equivalent replacement, improvement and supplement within the technical range disclosed by the present application, and any modification, equivalent replacement, improvement and supplement within the technical range disclosed by the present application, and any modification, equivalent replacement, improvement and supplement within the technical range disclosed by the present application, and any modification, equivalent replacement, improvement and supplement within the technical range disclosed by the present application, and any modification, equivalent replacement, improvement and supplement within the technical range disclosed by the present application, and any modification, equivalent replacement, improvement and supplement within the technical range disclosed by the present application, and any modification, equivalent replacement, improvement and supplement within the technical range disclosed by the present application, and any modification, equivalent replacement, improvement and supplement within the technical range disclosed by the present application, and any modification, equivalent replacement, improvement and supplement within

Claims

1. A method for the flow-casting preparation of multilayer fluorescent microcrystalline glass based on in-situ compounding, characterized in that, Specifically comprising the following steps: (1) preparing casting slurry: yellow fluorescent glass-ceramic slurry, red fluorescent glass-ceramic slurry and pure glass slurry are prepared respectively, the yellow fluorescent glass-ceramic slurry and the red fluorescent glass-ceramic slurry are prepared by mixing low-temperature transparent glass powder, fluorescent powder, dispersant, binder and organic solvent in a mass ratio and then centrifuging at high speed to remove bubbles; (2) in-situ casting and gradient drying: the yellow fluorescent glass-ceramic slurry prepared in step (1) is introduced into the first-stage doctor blade tank of the casting equipment, and after being shaped by the doctor blade, it is sent into the first-stage drying box, and after drying, it is sent to the second-stage casting with the conveying belt to obtain the first-stage green body; (3) the red fluorescent glass-ceramic slurry prepared in step (1) is introduced into the second-stage doctor blade tank of the casting equipment, and after in-situ composite casting with the first-stage green body prepared in step (2), it is sent into the second-stage drying box, and after drying, it is sent to the third-stage casting with the conveying belt to obtain the second-stage green body; (4) the pure glass slurry prepared in step (1) is introduced into the third-stage doctor blade tank of the casting equipment, and after in-situ composite casting with the second-stage green body prepared in step (3), it is sent into the third-stage drying box to form an integrated composite green body, and finally it is sent out with the conveying belt; (5) glue removal and sintering treatment: the integrated composite green body after drying is placed in a muffle furnace, and the temperature is first raised to 400-600℃ at a heating rate of 0.5-5℃ / min, the glue is removed for 4-20h, then the temperature is raised to 600-900℃, and the temperature is kept for 1-6h, and finally the temperature is cooled to room temperature, thereby obtaining a multi-layer fluorescent glass-ceramic composite luminescent material with a tight interface.

2. The in-situ composite based multilayered fluorescent glass-ceramic according to claim 1, wherein, Steps (2), (3) and (4) are repeated in turn, and a three-layer or more multi-layer fluorescent glass-ceramic composite structure can be casted.

3. The in-situ composite based multilayered fluorescent glass-ceramic production method by casting according to claim 1, characterized in that, In step (1), the chemical formula of the low-mid temperature transparent glass powder is: a1%SiO2-a2%P2O5-a3%B2O3-a4%Al2O3-a5%BaO-a6%CaO-a7%K2O-a8%Na2O, wherein 0 < a1 < 100, 0 < a2 < 100, 0 < a3 < 100, 0 < a4 < 100, 0 < a5 < 100, 0 < a6 < 100, 0 < a7 < 100, 0 < a8 < 100, and the ratio coefficient in the compound a1+a2+a3+a4+a5+a6+a7+a8=100, and the fluorescent powder is at least one of YAG:Ce, CaAlSiN3:Eu, CaSrAlSiN3:Eu, Lu3Al5O 12 :Ce.

4. The in-situ composite based multilayered fluorescent glass ceramic production method by casting according to claim 1, characterized in that, In step (1), the dispersant is ammonium polyacrylate or sodium hexametaphosphate, the binder is polyvinyl butyral or methyl cellulose, and the organic solvent is at least one of ethanol, acetone and oleic acid.

5. The in-situ composite based multilayered fluorescent glass ceramic production method by casting according to claim 1, characterized in that, The temperature of the drying box in steps (2), (3) and (4) is 50-100℃, and the winding speed of the conveying belt is 20-120cm / min.

6. The in-situ composite based multilayered fluorescent glass ceramic production method by casting according to claim 1, characterized in that, The base height of the doctor blade in steps (2), (3) and (4) is 100-300μm, and the height of the doctor blade in each subsequent casting process is increased by 50-200μm compared with the previous one, so that the thickness of each layer of the green body is controlled within 50-200μm.

7. The in-situ composite based multilayered fluorescent glass ceramic production method by casting according to claim 3, characterized in that: The chemical formula of the low-temperature transparent glass powder is: 55%SiO2-12%P2O5-18%B2O3-3.5%Al2O3-4%BaO-3%CaO-2.5%K2O-2%Na2O.